Financial Performance Analysis of PT. Pertamina Patra Niaga Regional Sulawesi 2013-2023 - A. Ghina Farah Adilah; Abd. Rakhman Laba; Andi Ratna Sari Dewi (STIE Amkop Makassar, 2024)
Financial Performance Analysis of PT. Pertamina Patra Niaga Regional Sulawesi 2013-2023 (Guided by Mr. Abd. Rakhman Laba and Mrs. Andi Ratna Sari Dewi). This research aims to analyzes the financial performance of PT. Pertamina Patra Niaga Regional Sulawesi 2013-2023. The analysis was carried out using financial ratio analysis methods. The ratios used include profitability, liquidity, solvency and activity ratios. Apart from that, this research also analyzes the development of financial performance using vertical and horizontal comparison methods of company financial reports during that period. The results of the analysis show that there are significant fluctuations in the financial performance of PT. Pertamina Patra Niaga, which is influenced by internal and external factors, such as changes in global oil prices and government policies regarding fuel subsidies. It is hoped that this research will provide insight for stakeholders regarding the company's financial health and provide recommendations for increasing efficiency and profitability in the future.